Evidence Based Decision Making-Rationale for Hospital Administrators - Medha Wadhwa; Pulkit Kalyan; Harshil Patel; Minesh Patel; Vedangee Joshi (Current Overview on Disease and Health Research Vol. 3, 2022)
Evidence-based management practice is an approach to decision-making and day-to day work practice that helps practitioners to critically evaluate the extent to which they can trust the evidence they have at hand. It also helps practitioners to identify, find and evaluate additional evidence relevant to their decisions. Furthermore, evidence-based management has been ignored in healthcare compared with evidence-based medicine. Unfortunately, leaders, policymakers, and managers, themselves, have no interest in applying this approach because of internal and external barriers to its use, such as the culture of decision-making based on evidence, managers’ lack of adequate knowledge about the research process, managers’ suspicions of the values of research and researchers, inadequate research dissemination, and a lack of external pressure for adopting researched practices. The objective of this chapter is to understand the rationale of evidence based practice to be implemented by Hospital Administrators.